Negative symptoms and speech pauses in youths at clinical high risk for psychosis - Stanislawski, Emma R.; Bilgrami, Zarina R.; Sarac, Cansu; Garg, Sahil; Heisig, Stephen; Cecchi, Guillermo A.; Agurto, Carla; Corcoran, Cheryl M. (NPJ schizophrenia, 2021)
Aberrant pauses are characteristic of schizophrenia and are robustly associated with its negative symptoms. Here, we found that pause behavior was associated with negative symptoms in individuals at clinical high risk (CHR) for psychosis, and with measures of syntactic complexity—phrase length and usage of determiners that introduce clauses—that we previously showed in this same CHR cohort to help comprise a classifier that predicted psychosis. These findings suggest a common impairment in discourse planning and verbal self-monitoring that affects both speech and language, and which is detected in clinical ratings of negative symptoms.